Achieving the ratiometric imaging of steroid sulfatase in living cells and tissues with a two-photon fluorescent probe. Issue 9 (6th January 2020) - Li, Wei; Yin, Shulu; Gong, Xiangyang; Xu, Wang; Yang, Ronghua; Wan, Yichao; Yuan, Lin; Zhang, XiaoBing
Abstract : A novel two-photon ratiometric fluorescence assay was proposed for monitoring endogenous steroid sulfatase (STS) activity, which achieved the ratiometric imaging of STS activity in the endoplasmic reticulum of living cells and tissues. Abstract : Herein, a novel two-photon ratiometric fluorescence assay was proposed for monitoring endogenous steroid sulfatase (STS) activity, which could be applied for the ratiometric imaging of STS activity in the endoplasmic reticulum of living cells and tissues and also could be used to distinguish estrogen-dependent tumor cells from other types of cells.